Attitudes toward ads portraying women in decorative roles and female competition: An evolutionary psychology perspective - Kyrousi, Antigone G.; Panigyrakis, George G.; Panopoulos, Anastasios P. (My University, 2016)
The portrayal of women in advertising is a prolific research topic and extant studies have emphasized the negative attitudes of female consumers toward stereotypic depictions of women in advertising in general. However, empirical evidence regarding female consumers’ responses to specific ads depicting women in decorative roles is scarce and conflicting. Drawing on the principles of evolutionary psychology, the present paper proposes that women’s attitudes toward such ads are underlied by the evolved context-sensitive mechanism of intrasexual competition. Relevant hypotheses are tested through two experimental studies. The findings indicate that decorative portrayals in advertising elicit more favorable attitudes when female consumers compete through a self-promotion strategy with regard to a competitor derogation one. Additionally, the temporal orientation of self-referencing during ad processing emerges as a moderator of the influence of the motivational state elicited by the medium context on attitudes.
Keywords: Advertising; Evolutionary psychology; Female stereotypes; Intrasexual competition